The University and the State. A Study into Global Transformations - Kwiek, Marek (Frankfurt and New York: Peter Lang, 2006)
This book argues that the current renegotiation of the postwar social contract concerning the welfare state in Europe is being accompanied by the renegotiation of a smaller-scale modern social pact between the university and the nation-state. Current transformations to the state under the pressures of globalization will not leave the university unaffected, and consequently it is useful to discuss the university and its future in the context of the state. In the new global order, against the odds, universities are striving to maintain their pivotal role in society. Their role as engines of economic growth and contributors to economic competitiveness between increasingly knowledge-driven economies is being widely acknowledged. But it is a radical reformulation of their traditional social roles. The main reasons for current transformations of the university include globalization pressures on nation-states and their public services, the end of the «Golden age» of the Keynesian welfare state, and the emergence of knowledge-based societies and knowledge-driven economies. Therefore the university can no longer be discussed solely in traditional, relatively self-contained disciplinary contexts. Here the university is seen from a variety of perspectives and through the lens of a wide range of disciplines (mainly educational sciences, political economy, sociology, political sciences, and philosophy). Contents Contents: The University in a Global Age - The University Between the State and the Market - The Idea of the University Revisited (the German Context) - The University and the Nation-State: the Impact of Global Pressures - The University and the Welfare State - Globalization, the Welfare State, and the Future of Democracy - The University and the New European Educational and Research Policies.
Keywords: higher education research; higher education policy; globalization and higher education; European universities; welfare state; National State; public sector reforms; higher education reforms; Central and Eastern Europe; European integration; Bologna Process; university governance; university funding; globalization and universities; europeanization; European Research Area; Higher Education Research Area; ERA; EHEA; German idea of the university; German Idealism; German Idealists; classical idea of the university; Wilhelm von Humboldt; Friedrich Schleiermacher; German Romantic; german idealist philosophy; welfare state models; globalization and welfare; globalists; globalization and the nation-state; Westphalian order; postcommunist transition; market reforms; marketization; globalists and skeptics; Ulrich Beck; Jurgen Habermas; Zygmunt Bauman; Welfare state reforms; welfare services; the university and the state; state-market; market forces; Johann Gottlieb Fichte; Friedrich Schelling; Karl Jaspers; new global order; modern pact; retreat of the welfare state; postnational constellation; capitalism and welfare state; Europe of knowledge; university missions; institutional change; transformations; Global transformations; Lehrfreiheit; Lernfreiheit; academic freedom; CEE countries; Eastern Europe; European higher education